Development of a novel nomogram-based online tool to predict axillary status after neoadjuvant chemotherapy in cN+ breast cancer: A multicentre study on 1, 950 patients. (December 2021) - Corsi, Fabio; Albasini, Sara; Sorrentino, Luca; Armatura, Giulia; Carolla, Claudia; Chiappa, Corrado; Combi, Francesca; Curcio, Annalisa; Della Valle, Angelica; Ferrari, Guglielmo; Gasparri, Maria Luisa; Gentilini, Oreste; et al.
Abstract: Background: Type of axillary surgery in breast cancer (BC) patients who convert from cN + to ycN0 after neoadjuvant chemotherapy (NAC) is still debated. The aim of the present study was to develop and validate a preoperative predictive nomogram to select those patients with a low risk of residual axillary disease after NAC, in whom axillary surgery could be minimized. Patients and methods: 1950 clinically node-positive BC patients from 11 Breast Units, treated by NAC and subsequent surgery, were included from 2005 to 2020. Patients were divided in two groups: those who achieved nodal pCR vs. those with residual nodal disease after NAC. The cohort was divided into training and validation set with a geographic separation criterion. The outcome was to identify independent predictors of axillary pathologic complete response (pCR). Results: Independent predictive factors associated to nodal pCR were axillary clinical complete response (cCR) after NAC (OR 3.11, p < 0.0001), ER-/HER2+ (OR 3.26, p < 0.0001) or ER+/HER2+ (OR 2.26, p = 0.0002) or ER-/HER2- (OR 1.89, p = 0.009) BC, breast cCR (OR 2.48, p < 0.0001), Ki67 > 14% (OR 0.52, p = 0.0005), and tumor grading G2 (OR 0.35, p = 0.002) or G3 (OR 0.29, p = 0.0003). The nomogram showed a sensitivity of 71% and a specificity of 73% (AUC 0.77, 95%CI 0.75–0.80). After external validation the accuracy of the nomogram was confirmed. Conclusion: The accuracy makes this freely-available, nomogram-based online tool useful to predict nodal pCR after NAC, translating the concept of tailored axillary surgery also in this setting of patients. Highlights: Axillary surgery after neoadjuvant chemotherapy in breast cancer is still debated. Several surgical approaches are reported but clear evidences are lacking. Prediction of axillary status after neoadjuvant chemotherapy is a clinical need. An nomogram was developed and validated to preoperatively identify ypN0 patients. This online tool could allow de-escalation of axillary surgery.